Free-Floating Car Rental Service in Riga and Customer Motivation: The Case of CARGURU - Karlis KRESLINS; Ion CARARUS; Marius ONOFREI; Tatjana VASILJEVA (Communications of International Proceedings, 2021)
The digitalization era has made a significant impact on the service industry, including banking, commerce and renting. Technology has converted traditional and formerly inseparable services into ones that can be used from any place and at any time. The paper explores customer motivators for using free-floating car rental service (FFCRS) in Riga with particular emphasis on utilitarian and hedonic motivators. A single case study design is used as the basis for the research methodology, which includes qualitative and quantitative data collected from other case studies, theoretical papers, in-depth interviews with company management and surveys of customers and non-users. Analysis of the findings reveals that there are four highly significant motivators – trust, driving disincentives, environmental consciousness and burden of ownership – which directly determine the frequency of CARGURU service usage.
Keywords: Free-floating Car Rental Service; Entrepreneurship; Customer Motivation